Optimizing Human Resource Development: Analyzing Differences in Job Satisfaction based on job diversity, Employee Status and generation at the Artificial Insemination Center - Ratna Fitri Hidayah; Hadi Sunaryo; Dwiyani Sudaryanti (Green Publisher Indonesia, 2024)
The Singosari Artificial Insemination Center (AIC) is a Technical Implementation Unit under the Ministry of Agriculture that has implemented the Public Service Agency Financial Management Pattern with the task and function of providing public services to all stakeholders. This study aims to analyze the level of employee job satisfaction and to determine the differences in employee job satisfaction based on job diversity, employee status and generation. This research is a mixed methods research conducted at AIC Singosari Malang Regency, East Java. using an instrument in form of a questionnaire distributed to 142 respondents using census sampling technique. This study uses descriptive analysis in the form of factor analysis and inferential analysis in the form of Mann Whitney Test and Kruskal Wallis Test. With the findings of seven dimensions of job satisfaction, namely the job itself, leadership, coworkers, promotions, work facilities and work environment in the high category and have the same job satisfaction category, which is quite satisfied on average. One indicator with a low score is the allowance indicator and there is a significant difference in job satisfaction based on Position and generation but there is an insignificant difference in job satisfaction between civil servants and non-civil servants. It is expected that AIC Singosari will always socialize and maintain transparency regarding the compensation structure for non-civil servants, including how wages and incentives are determined and distributed. Recognize differences in job security and benefits between civil servants and non-civil servants. As well as considering the desires and expectations between generations.